Strontium Promotes the Proliferation and Osteogenic Differentiation of Human Placental Decidual Basalis- and Bone Marrow-Derived MSCs in a Dose-Dependent Manner - Yi-Zhou Huang; Cheng-Guang Wu; Hui-Qi Xie; Zhao-Yang Li; Antonietta Silini; Ornella Parolini; Yi Wu; Li Deng; Yong-Can Huang (Hindawi Limited, 2019)
The osteogenic potential of mesenchymal stromal cells (MSCs) varies among different tissue sources. Strontium enhances the osteogenic differentiation of bone marrow-derived MSCs (BM-MSCs), but whether it exerts similar effects on placental decidual basalis-derived MSCs (PDB-MSCs) remains unknown. Here, we compared the influence of strontium on the proliferation and osteogenic differentiation of human PDB- and BM-MSCs in vitro. We found that 1 mM and 10 mM strontium, but not 0.1 mM strontium, evidently promoted the proliferation of human PDB- and BM-MSCs. These doses of strontium showed a comparable alkaline phosphatase activity in both cell types, but their osteogenic gene expressions were promoted in a dose-dependent manner. Strontium at doses of 0.1 mM and 1 mM elevated several osteogenic gene expressions of PDB-MSCs, but not those of BM-MSCs at an early stage. Nevertheless, they failed to enhance the mineralization of either cell type. By contrast, 10 mM strontium facilitated the osteogenic gene expression as well as the mineralization of human PDB- and BM-MSCs. Collectively, this study demonstrated that human PDB- and BM-MSCs shared a great similarity in response to strontium, which promoted their proliferation and osteogenic differentiation in a dose-dependent manner.